Emotional intelligence in adolescents (Journal of Parents and Teachers, 2013)
The article presents the importance of developing emotional skills during the early stages of the school levels and, especially during adolescence. To do so, it starts from the concept of emotional intelligence and the assessment by ability-based test. Later, we revised briefly the existing evidences about the impact of emotional intelligence in different field of personal, social and school functioning during adolescence.  Finally, we conclude with some recommendations for the EI development in adolescence through a new Spanish EI validated intervention developed by Emotional Lab at University of Málaga.
Keywords: Emotional Intelligence; Benefits; Adolescence; intervention; emotional functioning